COMMUNITY DEVELOPMENT AND EMPOWERMENT ABOUT THE FUNCTION OF THE MOSQUE AS A CENTRAL OF THE ACTIVITIES OF THE PEOPLE IN AL AMIN MOSQUE, PERUM GRIYA SURABAYA ASRI, SUMBEREJO DISTRICTS PAKAL, CITY SURABAYA - Dwi Indah Mustikorini; James Tumewu; Sukamto Sukamto (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
Another main function of the mosque is as a place of education people muslims . Education in the mosque is aimed at all ages, and covers all subjects, from Islam , science and art . Education carried out in mosques is to bring the younger generation closer to the mosque. Empowerment Public is one of the most important things for done in today 's era this , thing this caused role diverse strategic activity for resilience , independence and progress Public surroundings , especially in the field of religious , educational, social , cultural , economic Public local as well as implement government programs in skeleton acceleration of development programs , then how carry out education and empowerment Public with the mosque as central activity people around the mosque.